Socionomics how social mood shapes society - Ketovuori, Mikko (New York, NY Routledge, 2024)
"Socionomics: How Social Mood Shapes Society explores the main principles and applications of socionomic theory as elaborated by Robert Prechter. Socionomic theory posits that an omnipresent social mood, shifting constantly in a wave form through all aspects of society, is responsible for all social, economic and cultural phenomena, from fluctuations in the stock market to the popularity of particular genres of music at a given time. The social mood as an endogenous and collective force has its roots in the herding instinct often identified amongst crowds. While individuals typically make rational decisions when alone, in groups, mood-based mimetic behaviour can affect all the participants of the group. As social mood often goes unnoticed, people tend to give their collective feelings labels to rationalize them, thus constituting 'public opinion'. Therefore, whilst 'public opinion' as presented in the media is usually seen as rational, it is nevertheless based on the social context that often determines how people think. As the internet and social media have become ubiquitous in our daily lives, these herding instincts are spreading faster and faster than ever before and creating a pseudo-reality which can corrupt the collective perception of what is real and what is not. This stimulating and thought-provoking book will be of great interest to academics, practitioners, and policy makers with an interest in the humanities and social sciences, particularly sociology and economics"--
Includes bibliographical references and index.
Keywords: Interpersonal relationns; Economics -- Sociological aspects; Internet -- Social aspects; Social media -- Social aspects